SIRKULASI VIRUS AVIAN INFLUENZA SUBTIPE H5N1 DI PASAR TRADISIONAL DI JAWA TIMUR TAHUN 2012 - Risza Hartawan; NLP Indi Dharmayanti (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Avian influenza virus subtype H5N1 outbreak has become endemic in Indonesia since 2003. The disease does not only cause immense economic losses but it also leads to significant fatality of human being. The existence of traditional markets including live bird trading is suspected to play important role in the spreading and evolution of the virus. The objective of this study was to identify the circulation of H5N1 virus at traditional markets of East Java in 2012 by using reverse transcriptase polymerase chain reaction (RT-PCR) test and virus isolation. As results, this study detected the presence of the H5N1 virus circulating in Gresik, Mojokerto, Lamongan and Surabaya in both of live birds and environmental samples. The successfulness of virus isolation indicated a potential transmission to other hosts, including to human. This study suggests that the improvement of the poultry trading system at traditional markets by implementing sanitation, hygiene and biosecurity is necessary to reduce the burden of virus contamination at the market environment.